Strengthening Institutional Capacity of Guitar Cluster: Implementation of DEA and MACTOR - Muzakar Isa (Universitas Muhammadiyah Ponorogo, 2021)
This study aims to analyze the efficiency level of the use of guitar input and the output acquisition in guitar production and to analyze the influence and interests of stakeholders in the guitar industry. This study used a mixed-method approach. The research object is guitar business units that conduct production process, in which many business units only perform the production process with subcontracts from collectors and large producers. Efficiency and stakeholder analysis were used to determine the level of business efficiency and mapping of stakeholders in the guitar cluster. The results show the efficiency level of the guitar business was low. In general, the guitar business had not been efficient in using input and producing output. The inputs that led to the insufficient business were the number of labors and labor costs, while the outputs that caused inefficient business are turnover and profit of the business unit. The cluster organization needed to be improved by involving various key stakeholders in the development of guitar clusters and maintaining the sustainability of the guitar business.